EFEKTIVITAS PENGGUNAAN VIDEO “TUBUHKU BERHARGA” DAN BUKU CERITA BERGAMBAR TERHADAP PENINGKATAN PENGETAHUAN PENCEGAHAN KEKERASAN SEKSUAL PADA ANAK USIA DINI - Najwa Nursyabillah; Niken Meilani; Margono (Jurnal Ilmiah Kebidanan Imelda, 2025)
Cases of sexual violence against young children in Indonesia show an upward trend every year. Children's lack of knowledge about the forms and ways to prevent sexual violence is one of the main factors that make them vulnerable to becoming victims. This study aims to determine the effectiveness of educational media in the form of an animated video entitled “My Body is Precious” and a picture book in increasing knowledge about the prevention of sexual violence among young children. The study employed a quantitative method with a quasi-experimental pretest-posttest design with a control group. The research was conducted at TK ABA Dukuh I and TK ABA Mlangi, with a sample size of 70 children aged 5–6 years divided into two groups (video and picture book). The instrument used was a picture questionnaire filled out through direct interviews by the researcher. Data analysis used the Paired T-test and Independent T-test. The results showed an increase in knowledge scores in both groups, but a higher increase was found in the group given animated video media, with an average posttest score of 72.83 compared to 62.97 in the picture book group. Statistical tests indicated a significant difference (p=0.000). The conclusion of this study is that animated video media is more effective than picture storybooks in improving knowledge about the prevention of sexual violence in young children, making it an attractive, easy-to-understand, and relevant educational option for children.